2005
DOI: 10.1021/jp054155a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Oxygen Reduction Reaction Kinetics at (111)−(100) Nanofaceted Platinum Surfaces in Acidic Media

Abstract: The oxygen reduction reaction (ORR) was studied on CO-treated and untreated (111)-(100) nanofaceted platinum surfaces [Komanicky et al. J. Phys. Chem. 2005, 109, 23543] in sulfuric and perchloric acids using the rotating disk electrode technique. Activities of nanofaceted surfaces are found to be considerably higher than a simple average of the activities of (111) and (100) surfaces. We find that the high activity in sulfuric acid is consistent with the higher activity of (111) facets. It is due the weaker sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 19 publications
5
44
1
Order By: Relevance
“…Based on research on single-crystal basal planes, the adsorption of (bi)sulfate on (111) long range terraces strongly hinders the ORR, while the introduction of mono-atomic steps on 60 the surface, enhances the activity by breaking the long range order and thereby the anion adsorption strength. 10,49 Our results are consistent with this analysis, showing that facets close to (111) orientation with (100) contributions are the most active.…”
supporting
confidence: 90%
“…Based on research on single-crystal basal planes, the adsorption of (bi)sulfate on (111) long range terraces strongly hinders the ORR, while the introduction of mono-atomic steps on 60 the surface, enhances the activity by breaking the long range order and thereby the anion adsorption strength. 10,49 Our results are consistent with this analysis, showing that facets close to (111) orientation with (100) contributions are the most active.…”
supporting
confidence: 90%
“…The investigations, which have been mostly focused on the Pt single-crystal electrodes in a perchloric acid system, indicate that the E 1/2 of ORR polarization on Pt low-index facets is in the order of (110) > (111) > (100)2324. It is worth noting that the ORR activities can be greatly enhanced on the interlaced (111)-(100) Pt surfaces at the nanoscale, according to the study using the Pt model electrodes25. Most likely a synergetic effect between various facets promotes the overall performance of Pt catalysts: (100) facets can facilitate the adsorption of molecular oxygen (O 2 ), while the adsorbed O 2 may diffuse onto the neighbored (111) facets for successive reactions on which OH species have weaker adsorption25.…”
mentioning
confidence: 88%
“…Despite the progress in various alloys, it is well established that surface structure is a critical parameter to tune the activities of electrocatalysts in the ORR2425. Owing to this fact, it represents a major trend of research to establish the relationship between Pt surface structure and ORR activity.…”
mentioning
confidence: 99%
“…Several studies by the authors concern the effects of potential cycling on restructuring of the catalyst surface. While the phenomenon termed electrochemical annealing [75,76] is well known for a variety of different metals, for example, for Au and Cu crystals [17,[77][78][79] in halide-containing electrolytes and Ru and Pt crystals in COsaturated solution [74,[80][81][82][83][84], its influence on reactivity has been investigated less. In a study concerning the particle size effect of Pt with regard to CO oxidation, it was observed that potential cycling in CO-saturated solution (i.e., CO annealing) decreases the reactivity of the respective surface for CO stripping [73,74].…”
Section: Influence Of Surface Defects On Orrmentioning
confidence: 99%